Producing Television Programs Relevant To All Multi-cultural Society In Malaysia - Musa Abu Hassan; Fauziah Hassan; Rosidayu Sabran; Zulkiple Abd Ghani; Suria Hani A. Rahman (Universiti Putra Malaysia, 2024)
Like many countries, television enjoys a special interest among the society, even though information and communication technologies (ICT) have invaded the country. In 2010, the coverage of TV is about 75 percent of the population as compared to 77 percent of radio and 56 percent of newspapers. In the same year it was reported that adults spend 3.5 hours of watching TV per day as compared to 3 hours listening to radio and 2.4 hours engaging with Internet. The objectives of this paper are to examine the number of programs that were produced by TV stations in a week, and to identify the category of the programs produced by the stations. Data for this research was collected from published TV programs of the Free to Air (FTA) TV stations for a period of one week. Among others, the elements of TV program recorded were program genre, language, origin, duration of program, time of broadcast and target audience.The findings showed that each TV station has their own interest, target and focus in selecting and broadcasting TV programs to their audiences. Even though each TV station has fragmented their audience according to the language of TV programs, it is believed that the government’s effort to promote a harmony life in a multi-cultural society through TV programs is successful.